Water and Wastewater Treatment - Barbusiński, Krzysztof; Thomas, Maciej; Filipek, Krzysztof (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book presents an introductory editorial paper and publications referring to current problems and challenges in the field of wastewater treatment. The published articles cover a wide range of topics (reducing the concentration of hydrogen sulfide in biogas and decreasing release of phosphate into a sludge liquor at WWTPs; water ecosystem protection from antibiotics through the use of AOP methods; tertiary wastewater treatment in bio-filtration systems assisted by the addition of hydrogen peroxide to stimulate microbial activity; odor removal using biological methods; the impact of WWTPs on the environment by taking into account energy consumption, noise, and the formation of bioaerosols; and odor nuisances), which show significant progress in the research and implementation of innovative solutions in wastewater treatment technology.